2005
DOI: 10.1093/jnci/dji339
|View full text |Cite
|
Sign up to set email alerts
|

Paternity Following Treatment for Testicular Cancer

Abstract: Although the overall paternity rate after treatment for testicular cancer was high, the ability to conceive and the time to conception reflected the intensity of treatment. These data may help inform patients about their future ability to father biological children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
172
0
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(194 citation statements)
references
References 53 publications
10
172
0
12
Order By: Relevance
“…Secondly, we relate our end point to the number of patients reported having attempted parenthood. For male HLSs, the proportion of 45% who reported attempted parenthood is comparable to that observed in two studies of testicular cancer survivors (TCSs), where 31 and 39%, respectively, had tried to father a child following treatment (Rieker et al, 1990;Brydoy et al, 2005).…”
Section: Discussionsupporting
confidence: 67%
“…Secondly, we relate our end point to the number of patients reported having attempted parenthood. For male HLSs, the proportion of 45% who reported attempted parenthood is comparable to that observed in two studies of testicular cancer survivors (TCSs), where 31 and 39%, respectively, had tried to father a child following treatment (Rieker et al, 1990;Brydoy et al, 2005).…”
Section: Discussionsupporting
confidence: 67%
“…Chemotherapy has the greatest impact on fertility, followed by radiotherapy and retroperitoneal lymph node dissection (30,31). Fosså et al (28) reported that the paternity rate in 1,814 testicular cancer survivors was 71% and the duration from diagnosis until the birth of the first child after diagnosis was 6.6 years (28).…”
Section: Discussionmentioning
confidence: 99%
“…For example, until recently treatment of testicular cancer and Hodgkin disease had strong gonadotoxic side effects. The discovery of cisplatin-and non-alkylating agent-based therapies to treat these diseases offers not only a high cure rate, but also a high probability that patients spontaneously regain their fertility (38,39). Although the protocols are under constant review, presently it is unlikely that the treatment strategies for the most malignant diseases can be improved upon without diminishing their efficacy.…”
Section: New Clinically Relevant Technologies For Preservation Of Fermentioning
confidence: 99%